From localized periodic orbits to transients in pipe flow - Avila, Marc; Mellibovsky, Fernando; Roland, Nicolas; Hof, Björn (ETC 2013 - 14th European Turbulence Conference, 2013)
Hydrodynamic instability in wall bounded shear flows is abrupt and directly results in very complex spatio-temporal patterns even close to onset. This sudden scenario has challenged the application of dynamical systems concepts to describe the onset of turbulence. We present a bifurcation scenario leading from spatially localized relative periodic orbits to chaotic transients in pipe flow.
CRIS-Team Scopus Importer:2020-03-17